Strengthening Character Citizenship Through The Strengthening Program of Character Education Based on School Culture in Elementary Schools - Retnasari, Lisa; Hidayah, Yayuk; Prasetyo, Danang (Jurnal Ilmiah Sekolah Dasar, 2021)
The purpose of this study is to describe the school culture-based character education programs as a reinforcement of the citizenship character of students in elementary schools. The method used in this research is descriptive qualitative by collecting data in the form of interviews, observation and documentation. The research was conducted at SD N Ngrukeman Yogyakarta. Data analysis techniques using the triangulation of the Miles and Huberman methods. The results showed that the school culture-based character education programs as a reinforcement of the character of citizenship in students at SD N Ngrukeman Yogyakarta accustomed the main values of characters in the form of religious, nationalism, independent, mutual cooperation in various school cultural activities. In addition, there is support in the implementation of character education programs as an enhancer of the character of entrepreneurship in students at Ngrukeman Elementary School in Yogyakarta such as adequate infrastructure and teacher training. The conclusion of this article is that the school culture-based character education programs as a reinforcement of the citizenship character of students in elementary schools can be carried out with the cooperation of various parties in the school. The recommendation in this article is to be able to explore further about the school culture-based character education programs, especially in elementary schools.